Penentuan Harga Pokok Produksi Berdasarkan Harga Tranfer - Ardin Dolok Saribu; Anjeli Roulina Simanjuntak; Putri Yola Lumbantoruan; Yanti Enjelika Hutasoit; Yustina Siagian; Karnoan Marito Manullang; Yoga Xaferius Gurning; Romanty Hutasoit (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The limitations of traditional cost systems in capturing the complexity of operational activities lead to inaccuracies in cost allocation, which has an impact on the determination of cost of production and transfer prices between divisions. This study aims to evaluate the effectiveness of the Activity-Based Costing (ABC) method in improving the accuracy of cost information and examine the factors that affect its success. The method used is a literature study of major journals and supporting literature. The results of the study show that ABC is more accurate in allocating overhead costs based on relevant activities and cost drivers, and is able to reduce cost information distortion. The adoption of ABCs is influenced by cost structure, product diversification, and competitive intensity. However, successful implementation requires organizational readiness, managerial support, and an understanding of the operational context. These findings confirm the importance of implementing an adaptive cost system to support efficiency and transparency.